2018
DOI: 10.2147/opto.s151294
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of binocular function among pre- and early-presbyopes with asthenopia

Abstract: PurposeIndividuals approaching presbyopia may exhibit ocular symptoms as they contend with visual demands of near work, coupled with natural age-related changes in accommodation. Therefore, accommodation and vergence of 30- to 40-year-old, myopic, soft contact lens wearing subjects with symptoms of asthenopia and no history of using multifocal lenses were evaluated.Patients and methodsIn this prospective, observational study, 253 subjects with asthenopia were evaluated by 25 qualified practitioners, each at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
3
11
2
Order By: Relevance
“…While the impact of presbyopia can be minimised relatively easily by use of a visual correction, such as spectacles, contact lenses or refractive surgery (see section 5), these corrections have a financial burden (Naidoo et al, 2016) and it is estimated that globally over 50% of adults >50 years (up to over 50% of developing world where there is a lack of awareness and accessibility to affordable treatment options (Cheng et al, 2016;Girum et al, 2017;Hookway et al, 2016;Muhit et al, 2018;Schellini et al, 2016) and up to 34% even in developed countries) do not have adequate near correction, impacting task performance and productivity (Frick et al, 2015;Holden et al, 2008;Kaphle et al, 2016;Man et al, 2016;Nsubuga et al, 2016;Zebardast et al, 2017). Even in developed countries, increasing digital demands are associated with asthenopia, perhaps due to latent accommodative dysfunction, in people in their thirties, which is a form of largely undiagnosed early onset presbyopia (Reindel et al, 2018).…”
Section: Presbyopia Social and Economic Impactmentioning
confidence: 99%
“…While the impact of presbyopia can be minimised relatively easily by use of a visual correction, such as spectacles, contact lenses or refractive surgery (see section 5), these corrections have a financial burden (Naidoo et al, 2016) and it is estimated that globally over 50% of adults >50 years (up to over 50% of developing world where there is a lack of awareness and accessibility to affordable treatment options (Cheng et al, 2016;Girum et al, 2017;Hookway et al, 2016;Muhit et al, 2018;Schellini et al, 2016) and up to 34% even in developed countries) do not have adequate near correction, impacting task performance and productivity (Frick et al, 2015;Holden et al, 2008;Kaphle et al, 2016;Man et al, 2016;Nsubuga et al, 2016;Zebardast et al, 2017). Even in developed countries, increasing digital demands are associated with asthenopia, perhaps due to latent accommodative dysfunction, in people in their thirties, which is a form of largely undiagnosed early onset presbyopia (Reindel et al, 2018).…”
Section: Presbyopia Social and Economic Impactmentioning
confidence: 99%
“…It is reported that symptoms of asthenopia including irritating and tired eyes, blurred vision, and a dry eye sensation, accompany the pre- and early stages of presbyopia 54 . Therefore, the treatment of presbyopia may ameliorate those symptoms of asthenopia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the treatment of presbyopia may ameliorate those symptoms of asthenopia. The pre- and early stages of presbyopia, those can be detected by the measurement of the DCNFVA (distance-corrected near functional visual acuity) begin at about 30 years old 54 , 55 . It is interesting that our short-term experiment exhibited ameliorated effects on the lens elasticity of younger rats (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, abnormal binocular vision functions such as convergence insu ciency and divergence insu ciency could lead to asthenopia and visual discomfort. Nowadays, with the increasing use of digital media, demands on the binocular visual system are certainly increasing [2]. It was reported that sixty-three percent of the adults and eighteen percent of adolescents who spend long hours on digital devices had symptoms of asthenopi [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, with the increasing use of digital media, demands on the binocular visual system are certainly increasing [2]. It was reported that sixty-three percent of the adults and eighteen percent of adolescents who spend long hours on digital devices had symptoms of asthenopi [2,3]. Asthenopic symptoms, including burning, irritated, dry and tired eyes, blurred vision, eye fatigue and headache, are becoming increasing complaints of the patients in clinical practice.…”
Section: Introductionmentioning
confidence: 99%